PSI-26 The Effects of Probiotics on Growth and Metabolism in Ram Lambs - Trench, Alexis M (J Anim Sci, 2020)
Probiotic treatment can improve feed efficiency, increase growth, and alter blood components in small ruminants. Several commercial probiotics are available, but they vary in microorganisms resulting in different effects on growth and health. We hypothesized that Probios (Menomonie, Wisconsin) powder would increase growth, feed efficiency, and alter blood metabolites in ram lambs from 2 to 6 months of age. Twenty individually housed Shropshire ram lambs (average age 59.85 ± 2.74 days) were randomly assigned to a control or probiotic treatment group. Lambs were fed lamb concentrate (17.2% CP, 3.56 Mcal/kg) at 3.6% of their body weight and ad libitum hay (16.2% CP, 2.53 Mcal/Kg). Probios (10g) was fed once daily in concentrate of the probiotic group. Feed intake (FI) was determined daily and body weight (BW), body condition score (BCS), feed:gain (F:G), and average daily gain (ADG) were determined weekly. At weeks 0 and 16, heart girth (HG) and crown-rump length (CRL) were measured and ultrasonography of back fat (BF) and loin-eye area (LEA) was performed. Blood samples were collected biweekly. Week 16 blood metabolites were determined using Food Animal Maxi Panel (Missouri Veterinary Medical Diagnostic Laboratory). Plasma concentration of malondialdehyde (MDA) was determined at weeks 0, 6, and 16. Data were analyzed using SAS. Statistical significance was considered at P≤ 0.05. As a result of time, BW, BCS, ADG, FI, and F:G increased for all animals (P < 0.0001). No effect of treatment was observed for growth, feed efficiency, or oxidative stress measurements (P ≥ 0.33). Plasma albumin concentration increased by 12.66% (P = 0.02) and magnesium concentration increased by 5.83% (P = 0.01) as a result of treatment. Treatment had no effect on other measured blood metabolites. Probios powder did not alter growth but did alter blood metabolites in these lambs. Future studies should examine more effects of Probios on metabolism in growing lambs.